Impact of Mechanization of Cost and Return Structure of Paddy Cultivation in Krishnagiri District (International Journal of Psychosocial Rehabilitation, 2020)
Horticulture is the foundation of improvement in creating nations. It is a prevailing division in the Indian economy, both regarding its commitment to the all-out worth included just as a help base for work. It is seen that the ranchers of motorized homesteads execute the horticultural tasks more proficiently than the ranchers of non-automated ranches. This paper examines and thinks about the information yield structure of both the ranches of automated and non-motorized homesteads in order to empower them to discover the effect of motorization on ranch activities.